Application Development as Vaccination Information Distributing Media at Health Centers - Fauziah Nur Syifa; Aghnia Maulina; Mega Lestari (International Journal of Research and Applied Technology (INJURATECH), 2023)
Vaccines or immunizations aim for the human immune system to recognize and quickly fight bacteria or viruses that can cause infection. The purpose of developing this application is to optimize the role of the media as an educational platform and deliver information about vaccines to the public. The method used in the development of this application is Rapid Application Development (RAD). From this research, it is concluded that this application can have a positive impact on the community, such as the public can easily find out the vaccine schedule at the nearest health center, the existence of articles about vaccines that are following the facts can educate people who are still cloudy about the importance of vaccines. According to data, there are 1.76% of Bandung City residents have not vaccinated against Covid-19. In the end, this application was developed not only to convey information about the Covid-19 vaccine but also about other vaccines/immunizations. This application was developed to help the government program, namely the Healthy Indonesia Program.